2018
DOI: 10.1186/s13046-018-0678-6
|View full text |Cite
|
Sign up to set email alerts
|

The plant alkaloid tetrandrine inhibits metastasis via autophagy-dependent Wnt/β-catenin and metastatic tumor antigen 1 signaling in human liver cancer cells

Abstract: BackgroundTetrandrine is a bisbenzylisoquinoline alkaloid isolated from the Chinese medicinal herb Stephania tetrandra S. Moore. We previously demonstrated that tetrandrine exhibits potent antitumor effects in many types of cancer cells. In this study, we investigated the effects of tetrandrine on human hepatocellular carcinoma (HCC) metastasis.MethodsThe invasion and migration effects were evaluated via wound healing and transwell assays. Immunofluorescence and western blotting analyses were used to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…33 Autophagy has been reported to play multiple roles in cell metastasis, especially in the establishment of a pre-metastatic niche. 36 Consistent with these studies, our findings indicated that XAG suppressed HCC cell metastasis by inducing autophagic cell death. 34 Similarly, fluvastatin inhibited bone metastasis of lung adenocarcinoma by inducing autophagy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…33 Autophagy has been reported to play multiple roles in cell metastasis, especially in the establishment of a pre-metastatic niche. 36 Consistent with these studies, our findings indicated that XAG suppressed HCC cell metastasis by inducing autophagic cell death. 34 Similarly, fluvastatin inhibited bone metastasis of lung adenocarcinoma by inducing autophagy.…”
Section: Discussionsupporting
confidence: 88%
“…35 Zhang et al demonstrated that tetrandrine inhibited HCC metastasis through modulating the autophagy-dependent Wnt/β-catenin and MTA1 signaling, and autophagic cell death acted as a barrier against metastasis. 36 Consistent with these studies, our findings indicated that XAG suppressed HCC cell metastasis by inducing autophagic cell death.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…68 Processes of autophagy include mitophagy (for mitochondria), pexophagy (for peroxisomes), ER-phagy (for endoplasmic reticulum), or ribophagy (for ribosomes), depending on which organelles are targeted for specific autophagic degradation. 15,70,71 Pharmacological inhibitors of autophagy have been used extensively in various cellular conditions to delineate the molecular mechanism of autophagy and the effect of these inhibitors on autophagy. Under certain conditions, cells may undergo autophagic death, if intracellular survival pathways are blocked during autophagy.…”
Section: Cq Inhibits Lysosomal Acidificationmentioning
confidence: 99%